Diversity of Beautiful Beetles in the Suranadi Nature Tourism Park Area - Ilhamdi, Mohammad Liwa; Idrus, Agil Al; Santoso, Didik; Raksun, Ahmad; Kusuma, Anindita Suliya Hangesti Mandra (Jurnal Pijar Mipa, 2024)
Beetles exhibit unique shapes and color variations and play important ecological roles in the environment. Suranadi Nature Tourism Park (TWA Suranadi), a nature-based tourism area, has the potential presence of beautiful beetles. This study aims to examine the diversity of beautiful beetles in TWA Suranadi to support its tourism appeal. Sampling was conducted in May 2024 by surveying predetermined paths. The beetles collected were identified using identification books, relevant articles, and taxonomic name verification through websites. Thirteen species were identified, belonging to six families (Cerambycidae; Chrysomelidae, Erotylidae, Eucnemidae, Hydrophilidae, Scarabaeidae). The Chrysomelidae and Scarabaeidae families were species-rich and exhibited diverse shapes and colors. Beetles found along the forest edge path showed greater diversity (H’=2.3842) compared to the other two paths, namely the water path (H’=2.2893) and the middle path (H’=1.9804). The diversity (H’) of beautiful beetles in TWA Suranadi was 2.3532.